HER2-Specific Targeted Toxin DARPin-LoPE: Immunogenicity and Antitumor Effect on Intraperitoneal Ovarian Cancer Xenograft Model - Sokolova E. A. Evgeniya Aleksandrovna; Shilova O. N. Olga Nikolaevna; Kiselyova D. V. Darjya Vladimirovna; Shulga A. A. Aleksey Anatolievich; Balalaeva I. V. Irina Vladimirovna; Deev S. M. Sergey Mikhaylovich (2019, 2019)
Title screen